STRATEGI MENINGKATAN PENGUJUNG WISATA PADANGKUKU DESA LAMBUSANGO TIMUR KEBUPATEN BUTON - Elmin; Farid Yusuf Nur Achmad; La Asiri (Halu Oleo University, 2025)
This study aims to analyse the potential and challenges of tourism development in Padangkuku Tourism, Lambusango Timur Village, Buton Regency. This research uses a qualitative approach with a descriptive research design. Data was collected through interviews, field observations, and documentation analysis involving tourism managers, local communities, and tourists. The results show that Padangkuku has great strengths in terms of natural beauty and local culture, which can be major attractions for tourists. However, the main challenges faced are inadequate infrastructure and limited supporting facilities. The opportunities for developing digital-based tourism and ecotourism are significant, but competition with other more famous tourist destinations poses the main threat. In conclusion, tourism development in Padangkuku requires infrastructure improvements, facility enhancements, and digital marketing strategies to increase visitor numbers. Support from local government and active community involvement are essential for achieving sustainable tourism management.